BENEFITS OF CLINICAL PHARMACISTS PHARMACEUTICAL CARE INTERVENTION TO QUALITY OF PATIENT'S LIFE AND CONTROL HYPERTENSION - G, KARTHIKEYAN; D, RANGANAYAKULU (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Hypertension is a clinical condition of persistent raised arterial pressure, primarily due to increased vascular resistance in the systemic circulation. The main aim of this study was to investigate the benefits of clinical pharmacists' pharmaceutical care and treatment is, therefore, to prevent the damage to vital organs that cause clinical symptoms and increase mortality of the patients with hypertension. A cross-sectional prospective, randomized, controlled study was carried out in private hospitals in Tamil Nadu. Patients were asked six questions to understand about clinical pharmacist general communication and pharmaceutical care toward patients while buying. Out of 100 patients said 59% of the pharmacist always explains the things in an easy and understandable way to the patients, 62% of the staffs always show courtesy and average 61% always does care for the patients. In health and medicine related communication and counseling 48% of the staff talks to the patients about their health and the problems they are facing, and 50% of the pharmacist speaks to the patients about any side-effects; they are facing on taking the medicine. 55% of the staffs explain the new medicines in the prescription, and 53% explains the do's and dont's while taking the medicine and 54% explains the precautions to be taken if they face any side-effects. Average 52% answers are toward always and 35% says sometimes, 13% never interact with the patients. Over perception about the clinical pharmacists, 60% of the patients rated as good, 28% rated average and 12% of the people rated as poor. Keywords: Hypertension, Clinical pharmacy, Clinical pharmacists, Pharmaceutical care